Digital Rupiah Sebagai Katalisator Pertumbuhan Ekonomi di Sumatera: Analisis Potensi Provinsi di Sumatera - Muchlis, Fauziah; Muchlis, Akbar (Universitas Syiah Kuala, 2025)
Digital Rupiah, initiated under Bank Indonesia's Project Garuda, represent a pivotal advancement in the development of Central Bank Digital Currencies (CBDCs). This financial innovation has the potential to strengthen regional economic growth by improving payment systems, enhancing the effectiveness of monetary policy, and fostering economic integration, which are essential for provincial development. However, empirical studies examining the regional impacts of CBDCs remain limited. This research addresses this gap by analyzing the potential effects of Digital Rupiah implementation on the economic growth of Sumatras provinces. Using quarterly data from Q2 2020 to Q1 2024, the study investigates how these three factors influence economic growth of ten provinces in Sumatra. The results, based on Ordinary Least Squares estimation, indicate that North Sumatra demonstrates the highest potential for economic advancement, with all three variables exerting significant positive effects. These findings provide valuable insights for policy design and strategies to support post-pandemic recovery.